Penerapan Prinsip Desain Komunikasi Visual dalam Pelatihan Pembuatan Infografis dengan Canva bagi Guru PAUD Dadali - Pamela, Apsari Wiba; Aisyah, Najwa; Ramadinoto, Raden Daru (Indonesian Journal for Social Responsibility, 2025)
The rapid development of information technology demands continuous adaptation in the field of education, including at the Early Childhood Education (PAUD) level. One of the main challenges today is how to utilize engaging, effective learning media that align with the developmental characteristics of young children. At PAUD Dadali, challenges are still found in the use of infographics as learning media, primarily due to teachers’ limited understanding of visual communication design principles and their lack of skills in using graphic design software. This community service activity aims to provide training and assistance to PAUD Dadali teachers in creating infographics as learning media using the Canva application. Canva was chosen because it offers advantages over other graphic design tools, such as an easy-to-use interface and a wide selection of templates relevant to educational needs. These strengths make Canva a practical solution for teachers without a design background. The implementation methods included field interviews to identify partner needs, training planning and execution, and outcome evaluation. The training began with theoretical material on the basic principles of visual communication design, followed by a practical session using Canva. The results of the training show that participants acquired new skills in using Canva to create teaching materials. This is expected to enhance the quality of teaching at PAUD Dadali and support a more interactive and easily understandable learning process for young children.